On Competition and Regulation in Health Care Systems - Robert Nuscheler (Peter Lang International Academic Publishers, 2005)
Health care systems are under reform in many countries. This typically involves a shift towards more competition. But still, markets are highly regulated. This study analyzes competition and regulatory measures in four important fields using the modern tools of microeconomic theory and microeconometrics. The book demonstrates how price regulation interacts with the quality of care and shows that non-price competition amongst providers affects the social desirability of a gatekeeping system. Using data from the German Socio-Economic Panel, the conventional wisdom of risk selection by German sickness funds is challenged.
Keywords: 330